2011
DOI: 10.4103/0189-6725.91665
|View full text |Cite
|
Sign up to set email alerts
|

Meckel′s diverticulum in paediatric practice on Crete (Greece): A 10-year review

Abstract: All patients with MD underwent Meckel's diverticulectomy with appendicectomy. MD has an incidence of approximately 1 to 2% in our population. It is necessary to maintain a high index of suspicion in the diagnosis of MD paediatric age group because it can be easily misdiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
0
14
0
4
Order By: Relevance
“…The average age of the patients with intestinal haemorrhage was 2.1 years. Although haemorrhage is the most common complication in paediatric age with reported incidence as high as 50%,[28] but we observed a very low incidence. Menezes and Chen et al .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The average age of the patients with intestinal haemorrhage was 2.1 years. Although haemorrhage is the most common complication in paediatric age with reported incidence as high as 50%,[28] but we observed a very low incidence. Menezes and Chen et al .…”
Section: Discussionmentioning
confidence: 50%
“…had reported the incidence of haemorrhage as 55.5 and 39%, respectively. [2829] An Indian series by Mittal et al . had observed intestinal haemorrhage in 71.42% cases.…”
Section: Discussionmentioning
confidence: 99%
“…19, 20 Several prior studies have also shown successful resection of a Meckel diverticulum via diverticulectomy-only for children presenting with symptoms of bleeding. 13, 15 There are advantages of this approach, including the ease of diverticulectomy with laparoscopy and elimination of the need for an enterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…8 _ENREF_9 Of these, intussusception with MD as the leading point, followed by a mechanical volvulus of the small intestine around a persistent band that has attached the MD to the umbilicus, 8 _ENREF_10 are the most common.…”
Section: Discussionmentioning
confidence: 99%